Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2015-2018 - I Kadek Rubi Mulyana; Luh Kade Datrini; I.D.A.M. Manik Sastri (Jurnal Riset Akuntansi Warmadewa, 2021)
The research objective was to determine the effect of financial performance on stock returns in food and beverage companies listed on the Indonesia Stock Exchange for the 2015-2018 period. The number of samples is 9 companies over a period of 4 years, so the data is 36. The data source comes from secondary data in the form of annual financial reports that have been collected and published by the official website of the Indonesia Stock Exchange (IDX). Data analysis technique with multiple linear regression analysis. The results showed that the current ratio has no effect on stock returns, which is indicated by a significance value of 0.492 which is greater than 0.05, so H1 is rejected. Debt to Equity Ratio has no effect on Stock Return which is indicated by a significance value of 0.691 greater than 0.05, then H2 is rejected. Earning Per Share has an effect on Stock Return which is indicated by a significance value of 0.000 less than 0.05, then H3 is accepted. Return on Assets has an effect on Stock Return which is indicated by a significance value of 0.019 which is smaller than 0.05, then H4 is accepted.